Does Confucian culture affect public service motivation of grassroots public servants? Evidence from China - Duan, Cheche; Jiao, Jiaxin; Zhao, Chunzhen; Li, Yingying (Frontiers in Psychology, 2023)
Public service motivation contains distinctive cultural characteristics. The applicability of western culture-based public service motivation in the context of Chinese Confucian culture is one of the hot topics discussed. However, few empirical studies have focused on the specific relationship between Confucian cultural tradition and public service motivation. The current study collected 1225 representative questionnaires from 13 cities in central and eastern China, and adopted the Fixed Effect Model to verify six hypotheses. The empirical results in this study showed that Confucian culture has different effects on public service motivation from four dimensions, namely, Attraction to Politics and Policy Making (APP), Commitment to Public Interest (CPI), Compassion (COM) and Self-sacrifice (SS). The paternalistic leadership nurtured by the traditional Confucian culture also plays a part in moderating the influence of Confucian culture on public service motivation. Based on these findings, this study constructs a new theoretical model that expands the explanatory power of the theory of public service motivation in the cross-cultural management context, and provides valuable practical implications to highlight cultural differences in incentives for public servants in the Chinese public personnel management.